Code Switching in the Instructions of English Language Education Study Program Lecturers - Mukti, Thomas Wahyu Prabowo; Muljani, Retno (LLT Journal: A Journal on Language and Language Teaching, 2016)
Language is an essential mean of communication in teaching and learning activities. Specifically, in the English Language Education Study Program (ELESP) that employs English as the main instructional language for teaching and learning activities. Considering that English was not students first language, some lecturers employed code switching to help third-semester students in learning English. With regard to this phenomenon, this study addressed two research questions. First, what the types of code switching ELESP lecturers employ in their instructional languages are and second, what the reasons for ELESP lecturers to employ code switching in their instructional languages are. This study belonged to a basic interpretative study. It employed interview guidelines to understand the experiences of the lecturers who employed code switching. The results of this study showed that the lecturers employed both situational and metaphorical code switching. In addition, the writer found that the participants of the study code-switched for the reasons which can be classified into topic, addressee, emphasis, persuasion, solidarity, affection, nature of the subject and strategy. The results of the study also revealed that the use of code switching in lecturers instructional languages was mainly for the students understanding.